2004
DOI: 10.1002/job.269
|View full text |Cite
|
Sign up to set email alerts
|

Job and industry fit: the effects of age and gender matches on career progress outcomes

Abstract: SummaryUsing a sample of 232 MBA alumni, we tested the impact of respondent age, gender, and their interaction on career progress outcomes (managerial level, number of promotions, and salary) and whether age-and gender-type of contexts moderated these relationships. Women's salaries did not increase much with age, whereas men's salaries showed a marked increase with age. We also found a gender  job gender-type effect on salary, such that women earned somewhat higher salaries in masculine-typed jobs, while men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 72 publications
3
58
0
Order By: Relevance
“…Our results indicate that women were less satisfied with the benefits of their MBA education, less positive about their school program and support services, and more concerned with the cost of an MBA education. The greater concern with program costs is not surprising because it has been shown that women generally reap less benefit from MBA degrees (Dreher et al, 1985; Goldberg et al, 2004; Miree & Frieze, 1999; Simpson, 2000; Simpson et al, 2005) and even may have to change organizations to reap any benefit they could obtain from the degree (Simpson, 2000; Sturges et al, 2003). One explanation for the concerns regarding costs may be the stations in life during which women and men begin to consider graduate business education.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results indicate that women were less satisfied with the benefits of their MBA education, less positive about their school program and support services, and more concerned with the cost of an MBA education. The greater concern with program costs is not surprising because it has been shown that women generally reap less benefit from MBA degrees (Dreher et al, 1985; Goldberg et al, 2004; Miree & Frieze, 1999; Simpson, 2000; Simpson et al, 2005) and even may have to change organizations to reap any benefit they could obtain from the degree (Simpson, 2000; Sturges et al, 2003). One explanation for the concerns regarding costs may be the stations in life during which women and men begin to consider graduate business education.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite our position on the age‐performance effect, we believe that age does influence other relevant considerations in an MBA education. Recent research suggests younger MBA students are more likely than older students to see the degree as a tool for career enhancement and advancement (Simpson et al, 2005; Thompson & Gui, 2000) and are more likely to be promoted as a result of pursuing the degree (Goldberg, Finkelstein, Perry, & Konrad, 2004). In other words, older students generally do not see the MBA degree to be as beneficial to advancing their careers, as do younger students, and in fact are less likely than younger students to be promoted based on their MBA degrees.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, we took high and low levels as the following: ‘high – suppliers, employees, banks, and other creditors have lost a total of 500,000 euros as a result of the business failure’; and ‘low – suppliers, employees, banks, and other creditors have lost a total 5,000 euros as a result of the business failure’. Second, because some sectors are seen as more masculine than others (Garcia‐Retamero and López‐Zafra, ; Goldberg et al., ), we also included an attribute about the industry sector of the failed business: ‘clothing manufacturing – the entrepreneur's business was manufacturing shirts, dresses, and skirts’; and ‘electronics manufacturing – the entrepreneur's business was manufacturing electronic devices for mobile phones and television sets’. Third, given that there is evidence of gender prejudice in the workplace (Garcia‐Retamero and López‐Zafra, ), we also used the attribute describing the gender of the target entrepreneur as a control.…”
Section: Methodsmentioning
confidence: 99%
“…Women in the U.S. technology and engineering workforce receive lower salaries than their male counterparts with similar education and qualifications (Gaudin, 2003;Lal, Yoon, & Carlson, 1999;Sumner & Niederman, 2004). Further, these salaries show a much slower growth as compared to that of men (Goldberg, Finkelstein, Perry, & Konrad, 2004). Female representation in managerial IT positions is disproportionately lower compared to men (Igbaria & Baroudi, 1995;Truman & Baroudi, 1994) since women often encounter a "glass ceiling" effect in midlevel positions.…”
Section: Gender Stereotyping and Discrimination In The Workplacementioning
confidence: 99%